A carbon molecular sieve and its preparation method
By adding zinc -manganese double metal organic framework materials during the preparation of carbon molecular sieves, Ti3C2TXMXENE nanosimal tablets and urea, combined with the advantages of polymer materials to solve the problem of low capacity of carbon molecular sieve and poor stability, prepare high -performance carbon molecular sieves Adsorption agent has excellent gas adsorption and separation performance.
Patent Information
- Application Number
- CN202411554126.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The existing carbon molecular sieve has problems such as low adsorption capacity, single surface chemistry and poor material stability in gas adsorption and separation, which limits its scale and further development in industrial applications.
By using metal zinc and manganese and 2,5-dihydroxyl pheneinic acid reactions to synthesize zinc-manganese bipolar organic frame materials, and add Ti3C2TXMXENE nanoscopic tablets and urea during the synthesis process, prepare composite materials, combined with the advantages of polymer materials , Prepare high -performance carbon -molecular sieve adsorption agents.
Improving the surface area and pore structure of carbon molecular sieves, enhance the absorption and separation ability of the gas, improve the stability and pressure resistance of the material, and improve the adsorption performance of carbon dioxide, and have good repetitiveness and regeneration performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas adsorption separation, and in particular relates to a carbon molecular sieve and a preparation method thereof. Background Art
[0002] Carbon molecular sieves have the advantages of large specific surface area, high porosity, uniform pore size distribution, good acid and alkali resistance, easy access, low price and high thermal stability. They can be widely used in adsorption separation, gas purification and other fields. Compared with other porous carbon materials, carbon molecular sieves show higher selectivity and are widely used in the separation of gas mixtures. At present, carbon molecular sieves are usually obtained by high-carbon content material through high-temperature heat treatment. The precursors for their preparation come from a wide range of sources, mainly including organic polymers (polyfurfuryl alcohol, phenolic resin, polyimide, etc.), coal and its derivatives (peat, anthracite, coal coke, etc.) and biomass (nut shells, wood, plant cellulose, etc.). The cost of coal and its derivatives is low, but the impurities they contain are high. Due to the difference in coal quality, the stability of carbon molecular sieves is poor and the adsorption capacity of the prepared carbon molecular sieves for gas is relatively low.
[0003] Metal-organic framework materials are a new type of porous material with metal ions as connection points and organic ligands as support to form a three-dimensional periodic network structure. Due to its advantages such as crystallinity, diverse and controllable structure, it has become a new generation of porous materials after zeolites and carbon nanotubes. It has wide application value in catalysis, energy storage and separation. However, since the adsorption and separation of carbon dioxide requires multiple repeated adsorption and desorption processes, the porosity of its internal organization can easily cause the collapse of the internal structure and reduce the specific surface area and adsorption capacity. In addition, most existing carbon materials are synthetic materials with a high carbon content made by high-temperature pyrolysis and carbonization of polymers under the protection of inert gas. They have special properties such as high temperature resistance and high strength, but due to the harsh conditions of high-temperature pyrolysis, the main structure often collapses, resulting in defects such as variations in pore size morphology. In addition, due to the limitations of factors such as the material and structural characteristics of conventional carbon molecular sieves, they have problems such as low adsorption capacity and single surface chemical properties in gas adsorption and separation, which greatly limits the large-scale application of carbon molecular sieves in gas adsorption and separation. Moreover, due to the great brittleness of the material, its further industrial application is limited to some extent. Summary of the invention
[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a carbon molecular sieve and a preparation method thereof, wherein a zinc-manganese bimetallic organic framework material is synthesized by reacting metal zinc and manganese with a ligand 2,5-dihydroxyterephthalic acid, and Ti3C2T is added during the synthesis process. xMXene nanosheets and urea are made into composite materials, and then the advantages of composite materials and polymer materials are combined to prepare high-performance carbon molecular sieve adsorbents.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A carbon molecular sieve comprises a composite material and a polymer material. The composite material is a zinc-manganese bimetallic organic framework material synthesized by reacting metal zinc and manganese with a ligand 2,5-dihydroxyterephthalic acid, and Ti3C2T is added during the synthesis process. x The MXene nanosheets are made of urea; the polymer material is one of polyimide polymers, polysulfone polymers and polyethersulfone polymers.
[0007] Preferably, the method for preparing the composite material comprises the following steps:
[0008] (1) Lithium fluoride was dissolved in concentrated hydrochloric acid and stirred for 20-30 min. Then titanium carbide aluminum powder was added and stirred at 30-40 °C for 20-24 h. After the reaction was completed, the mixture was centrifuged and washed with deionized water until neutral. The aqueous suspension of the precipitate was ultrasonically treated, centrifuged and dried to prepare Ti3C2T x MXene nanosheets;
[0009] (2) Mix N,N-dimethylformamide, anhydrous ethanol and deionized water evenly, then add zinc nitrate hexahydrate and manganese dichloride tetrahydrate, mix evenly, add 2,5-dihydroxyterephthalic acid, and mix by ultrasonic for 20-30 minutes to obtain solution 1. Take Ti3C2T x MXene nanosheets are dispersed in deionized water to obtain a suspension. Solution 1 is added to the suspension and stirred for 15 to 30 minutes to obtain solution 2. Urea solution is added to solution 2 and stirred for 10 to 30 minutes to obtain solution 3. Solution 3 is transferred to a polytetrafluoroethylene-lined reactor and reacted at 120 to 145°C for 20 to 24 hours. After the reaction is completed, it is cooled to room temperature. The precipitate obtained by centrifugation is washed and dried to prepare a composite material.
[0010] Preferably, the concentration of the urea solution is 0.1-0.5 mol / L.
[0011] Preferably, the concentration of concentrated hydrochloric acid in step (1) is 8-10 mol / L, and the mass ratio of lithium fluoride to titanium aluminum carbide is 1:1-1.5.
[0012] Preferably, in step (2), the volume ratio of N,N-dimethylformamide, anhydrous ethanol and deionized water is 12-17:1-1.25:1.
[0013] Preferably, in step (2), zinc nitrate hexahydrate, manganese dichloride tetrahydrate, 2,5-dihydroxyterephthalic acid, Ti3C2T x The addition ratio of MXene nanosheets and urea solution is 1.7~1.8g:1.12~5.64g:0.56~0.9g:0.1~0.5g:5~10mL.
[0014] A method for preparing the carbon molecular sieve as described above comprises the following steps: uniformly dispersing a composite material and a polymer material in N,N-dimethylformamide, reacting at 60-120°C for 18-24 hours, centrifuging, washing and drying after the reaction is completed, calcining the obtained product under nitrogen protection at a calcination temperature of 400-1000°C for 4-6 hours to prepare a carbon molecular sieve.
[0015] Preferably, the mass ratio of the composite material to the polymer material is 2-5:1.
[0016] Preferably, the heating rate of the calcination is 4-6°C / min.
[0017] Beneficial effects of the present invention:
[0018] The present invention synthesizes bimetallic MOF-74 material by reacting metal zinc and manganese with ligand 2,5-dihydroxyterephthalic acid, which has excellent specific surface area and pore structure, is conducive to gas absorption and separation, and Ti3C2T is added during the synthesis process. x MXene nanosheets and urea to prepare a composite material. Ti3C2T x The rich active surface of MXene nanosheets can be used as a carrier of Zn-Mn bimetallic organic framework materials, which is conducive to the stable loading and dispersion of Zn-Mn bimetallic organic framework materials, avoiding the occurrence of agglomeration, and avoiding the collapse of the internal structure of Zn-Mn bimetallic organic framework materials to reduce the specific surface area and adsorption capacity, thereby improving the stability of the material. x The mechanical properties of MXene nanosheets are endowed to zinc-manganese bimetallic organic framework materials, thereby improving the compressive strength of carbon molecular sieves. Nitrogen in urea is introduced as a heteroatom. Since the radius of nitrogen atoms is very close to that of carbon atoms, the introduction of nitrogen atoms will not destroy the original skeleton structure of the zinc-manganese bimetallic organic framework material. Nitrogen atoms and carbon dioxide can be combined with each other through hydrogen bonds, polarization, electrostatic fields and acid-base effects, thereby effectively improving the adsorption performance of carbon dioxide. The material is easy to regenerate and has good repeatability. The present invention combines the advantages of composite materials and polymer materials to prepare a high-performance porous carbon molecular sieve adsorbent, which has potential application value in the field of gas storage and separation. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Example 1 A method for preparing a composite material comprises the following steps:
[0021] (1) 1 g of lithium fluoride was dissolved in 20 mL of 9 mol / L concentrated hydrochloric acid and stirred for 30 min. Then 1 g of titanium carbide aluminum powder was added and stirred at 35 °C for 24 h. After the reaction was completed, the mixture was centrifuged and washed with deionized water until neutral. The aqueous suspension of the precipitate was ultrasonically treated, centrifuged, and dried to prepare Ti3C2T x MXene nanosheets;
[0022] (2) Take 150 mL of N, N-dimethylformamide, 10 mL of anhydrous ethanol and 10 mL of deionized water and mix them evenly. Then add 1.7 g of zinc nitrate hexahydrate and 1.98 g of manganese dichloride tetrahydrate. After mixing evenly, add 0.75 g of 2,5-dihydroxyterephthalic acid and mix them ultrasonically for 30 min to obtain solution 1. Take 0.2 g of Ti3C2T x MXene nanosheets were dispersed in 20 mL of deionized water to obtain a suspension. Solution 1 was added to the suspension and stirred for 20 min to obtain solution 2. 10 mL of 0.1 mol / L urea solution was added to solution 2 and stirred for 20 min to obtain solution 3. Solution 3 was transferred to a polytetrafluoroethylene-lined reactor and reacted at 140 °C for 24 h. After the reaction was completed, it was cooled to room temperature. The precipitate obtained by centrifugation was washed and dried to prepare a composite material.
[0023] Example 2 A method for preparing a composite material comprises the following steps:
[0024] (1) 1 g of lithium fluoride was dissolved in 20 mL of 9 mol / L concentrated hydrochloric acid and stirred for 30 min. Then 1 g of titanium carbide aluminum powder was added and stirred at 35 °C for 24 h. After the reaction was completed, the mixture was centrifuged and washed with deionized water until neutral. The aqueous suspension of the precipitate was ultrasonically treated, centrifuged, and dried to prepare Ti3C2T x MXene nanosheets;
[0025] (2) Take 120 mL of N, N-dimethylformamide, 12 mL of anhydrous ethanol and 10 mL of deionized water and mix them evenly. Then add 1.7 g of zinc nitrate hexahydrate and 3.38 g of manganese dichloride tetrahydrate. After mixing evenly, add 0.75 g of 2,5-dihydroxyterephthalic acid and mix them ultrasonically for 30 min to obtain solution 1. Take 0.3 g of Ti3C2T x MXene nanosheets were dispersed in 20 mL of deionized water to obtain a suspension. Solution 1 was added to the suspension and stirred for 25 min to obtain solution 2. 5 mL of 0.4 mol / L urea solution was added to solution 2 and stirred for 30 min to obtain solution 3. Solution 3 was transferred to a polytetrafluoroethylene-lined reactor and reacted at 135 °C for 24 h. After the reaction was completed, it was cooled to room temperature. The precipitate obtained by centrifugation was washed and dried to prepare a composite material.
[0026] Example 3 A method for preparing a composite material comprises the following steps:
[0027] (1) 1 g of lithium fluoride was dissolved in 20 mL of 9 mol / L concentrated hydrochloric acid and stirred for 30 min. Then 1 g of titanium carbide aluminum powder was added and stirred at 35 °C for 24 h. After the reaction was completed, the mixture was centrifuged and washed with deionized water until neutral. The aqueous suspension of the precipitate was ultrasonically treated, centrifuged, and dried to prepare Ti3C2T x MXene nanosheets;
[0028] (2) Take 160 mL of N, N-dimethylformamide, 10 mL of anhydrous ethanol and 10 mL of deionized water and mix them evenly. Then add 1.7 g of zinc nitrate hexahydrate and 4.51 g of manganese dichloride tetrahydrate. After mixing evenly, add 0.75 g of 2,5-dihydroxyterephthalic acid and mix them ultrasonically for 30 min to obtain solution 1. Take 0.5 g of Ti3C2T x MXene nanosheets were dispersed in 20 mL of deionized water to obtain a suspension. Solution 1 was added to the suspension and stirred for 30 min to obtain solution 2. 5 mL of 0.5 mol / L urea solution was added to solution 2 and stirred for 30 min to obtain solution 3. Solution 3 was transferred to a polytetrafluoroethylene-lined reactor and reacted at 145 °C for 24 h. After the reaction was completed, it was cooled to room temperature. The precipitate obtained by centrifugation was washed and dried to prepare a composite material.
[0029] Example 4 A method for preparing a carbon molecular sieve comprises the following steps: uniformly dispersing the composite material prepared in Example 1 and polyimide P84 in N,N-dimethylformamide, wherein the mass ratio of the composite material to polyimide P84 is 4:1; reacting at 80°C for 20 hours; centrifuging, washing and drying after the reaction is completed; calcining the obtained product under nitrogen protection, wherein the calcination temperature is 800°C, the heating rate is 5°C / min, and the calcination time is 4 hours to prepare a carbon molecular sieve.
[0030] Example 5 A method for preparing a carbon molecular sieve, wherein an equal amount of the composite material in Example 4 is replaced by the composite material prepared in Example 2, and other conditions are the same as in Example 4.
[0031] Example 6 A method for preparing a carbon molecular sieve, wherein an equal amount of the composite material in Example 4 is replaced by the composite material prepared in Example 3, and other conditions are the same as in Example 4.
[0032] Comparative Example 1 A method for preparing a composite material comprises the following steps:
[0033] (1) 1 g of lithium fluoride was dissolved in 20 mL of 9 mol / L concentrated hydrochloric acid and stirred for 30 min. Then 1 g of titanium carbide aluminum powder was added and stirred at 35 °C for 24 h. After the reaction was completed, the mixture was centrifuged and washed with deionized water until neutral. The aqueous suspension of the precipitate was ultrasonically treated, centrifuged, and dried to prepare Ti3C2T x MXene nanosheets;
[0034] (2) Take 150 mL of N, N-dimethylformamide, 10 mL of anhydrous ethanol and 10 mL of deionized water and mix them evenly. Then add 1.7 g of zinc nitrate hexahydrate and 1.98 g of manganese dichloride tetrahydrate. After mixing evenly, add 0.75 g of 2,5-dihydroxyterephthalic acid and mix them by ultrasonic mixing for 30 min to obtain solution 1. Take 10 mL of 0.1 mol / L urea solution and add it to solution 1. Continue stirring for 20 min to obtain solution 2. Transfer solution 2 to a polytetrafluoroethylene-lined reactor and react at 140 °C for 24 h. After the reaction is completed, cool to room temperature. Wash and dry the precipitate obtained by centrifugation to prepare a composite material.
[0035] Comparative Example 2 A method for preparing a composite material comprises the following steps:
[0036] (1) 1 g of lithium fluoride was dissolved in 20 mL of 9 mol / L concentrated hydrochloric acid and stirred for 30 min. Then 1 g of titanium carbide aluminum powder was added and stirred at 35 °C for 24 h. After the reaction was completed, the mixture was centrifuged and washed with deionized water until neutral. The aqueous suspension of the precipitate was ultrasonically treated, centrifuged, and dried to prepare Ti3C2T x MXene nanosheets;
[0037] (2) Take 150 mL of N, N-dimethylformamide, 10 mL of anhydrous ethanol and 10 mL of deionized water and mix them evenly. Then add 1.7 g of zinc nitrate hexahydrate and 1.98 g of manganese dichloride tetrahydrate. After mixing evenly, add 0.75 g of 2,5-dihydroxyterephthalic acid and mix them ultrasonically for 30 min to obtain solution 1. Take 0.2 g of Ti3C2T x MXene nanosheets were dispersed in 20 mL of deionized water to obtain a suspension. Solution 1 was added to the suspension and stirred for 20 min to obtain solution 2. Solution 2 was transferred to a polytetrafluoroethylene-lined reactor and reacted at 140 °C for 24 h. After the reaction was completed, it was cooled to room temperature. The precipitate obtained by centrifugation was washed and dried to prepare a composite material.
[0038] Comparative Example 3 A method for preparing a carbon molecular sieve, wherein an equal amount of the composite material in Example 4 is replaced by the composite material prepared in Comparative Example 1, and other conditions are the same as in Example 4.
[0039] Comparative Example 4 A method for preparing a carbon molecular sieve, wherein an equal amount of the composite material in Example 4 is replaced by the composite material prepared in Comparative Example 2, and other conditions are the same as in Example 4.
[0040] Comparative Example 5 A method for preparing a carbon molecular sieve is provided. Polyimide P84 is calcined under nitrogen protection at a calcination temperature of 800° C., a heating rate of 5° C. / min, and a calcination time of 4 h to prepare a carbon molecular sieve.
[0041] Performance Testing
[0042] The carbon molecular sieves prepared in Examples 4-6 and Comparative Examples 3-5 were subjected to performance testing to test their adsorption capacity for carbon dioxide and nitrogen. The adsorption test of carbon dioxide and nitrogen was tested using an Autosorb-iQ-MP instrument using a static capacity method. Before the test, the sample was vacuum degassed at 150°C for 6 hours to remove the adsorbent surface occupied by non-adsorbent molecules as much as possible, so that the prepared carbon molecular sieve could adsorb as much carbon dioxide and nitrogen as possible. The test pressure condition was 1atm, the test temperature was 25°C, and 5 carbon dioxide cycle tests were performed; 5 carbon molecular sieves prepared in Examples 4-6 and Comparative Examples 3-5 were randomly selected for compressive strength testing, and the compressive strength was represented by the axial breaking pressure of the sample. The data results are shown in Table 1.
[0043] Table 1 Sample performance test results
[0044]
[0045] As can be seen from the data results in Table 1, the carbon molecular sieves prepared in Examples 4-6 of the present invention have higher carbon dioxide adsorption capacity and high compressive strength than Comparative Examples 3-5. After 5 cycles, the carbon dioxide adsorption capacity did not show a significant decrease, indicating that the carbon molecular sieves prepared in Examples 4-6 are a kind of adsorbent with a large and stable adsorption capacity, and are excellent adsorbent materials for adsorbing carbon dioxide, and the introduction of MXene nanosheets and urea will not reduce the regeneration performance of the material. Wherein the composite material added in Comparative Example 3 does not introduce MXene nanosheets, and the carbon dioxide adsorption capacity, carbon dioxide adsorption capacity after circulation and compressive strength are measured to be lower than those in Examples 4-6, indicating that the addition of MXene nanosheets can improve the adsorption capacity and compressive strength of carbon molecular sieves, and the repeatability is good. The composite material added in Comparative Example 4 does not introduce urea, and the carbon dioxide adsorption capacity and carbon dioxide adsorption capacity after circulation are measured to be lower than those in Examples 4-6, indicating that the introduction of nitrogen atoms effectively improves the adsorption performance of the material for carbon dioxide, and the compressive strength is not significantly changed compared with Examples 4-6, indicating that nitrogen doping in urea does not destroy the compressive strength of the material, and no composite material is added in Comparative Example 5, and its performance is most significantly reduced compared with Examples 4-6.
[0046] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0047] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A carbon molecular sieve, characterized in that: The composite material comprises a composite material and a polymer material. The composite material is synthesized by reacting metal zinc and manganese with a ligand 2,5-dihydroxyterephthalic acid to form a zinc-manganese bimetallic organic framework material, and Ti3C2T x MXene nanosheets and urea; the polymer material is one of polyimide polymers, polysulfone polymers, and polyethersulfone polymers; The preparation method of the composite material comprises the following steps: (1) Lithium fluoride was dissolved in concentrated hydrochloric acid and stirred for 20-30 min. Then titanium carbide aluminum powder was added and stirred at 30-40 °C for 20-24 h. After the reaction was completed, the mixture was centrifuged and washed with deionized water until neutral. The aqueous suspension of the precipitate was ultrasonically treated, centrifuged and dried to prepare Ti3C2T x MXene nanosheets; (2) Mix N,N-dimethylformamide, anhydrous ethanol and deionized water evenly, then add zinc nitrate hexahydrate and manganese dichloride tetrahydrate, mix evenly, add 2,5-dihydroxyterephthalic acid, and mix by ultrasonic for 20-30 minutes to obtain solution 1. Take Ti3C2T x MXene nanosheets are dispersed in deionized water to obtain a suspension, solution one is added to the suspension and stirred for 15 to 30 minutes to obtain solution two, urea solution is added to solution two, stirring is continued for 10 to 30 minutes to obtain solution three, solution three is transferred to a polytetrafluoroethylene-lined reactor, reacted at 120 to 145°C for 20 to 24 hours, cooled to room temperature after the reaction is completed, and the precipitate obtained by centrifugation is washed and dried to prepare a composite material; The preparation method of the carbon molecular sieve comprises the following steps: uniformly dispersing the composite material and the polymer material in N,N-dimethylformamide, reacting at 60-120°C for 18-24h, centrifuging, washing and drying after the reaction is completed, calcining the obtained product under nitrogen protection, the calcination temperature is 400-1000°C, and the calcination time is 4-6h to prepare the carbon molecular sieve.
2. The carbon molecular sieve according to claim 1, characterized in that The concentration of the urea solution is 0.1-0.5 mol / L.
3. The carbon molecular sieve according to claim 1, characterized in that The concentration of concentrated hydrochloric acid in step (1) is 8-10 mol / L, and the mass ratio of lithium fluoride to titanium aluminum carbide is 1:1-1.
5.
4. The carbon molecular sieve according to claim 1, characterized in that In the step (2), the volume ratio of N,N-dimethylformamide, anhydrous ethanol and deionized water is 12-17:1-1.25:
1.
5. The carbon molecular sieve according to claim 1, characterized in that In step (2), zinc nitrate hexahydrate, manganese dichloride tetrahydrate, 2,5-dihydroxyterephthalic acid, Ti3C2T x The addition ratio of MXene nanosheets and urea solution is 1.7~1.8g:1.12~5.64g:0.56~0.9g:0.1~0.5g:5~10mL.
6. The carbon molecular sieve according to claim 1, characterized in that The mass ratio of the composite material to the polymer material is 2-5:
1.
7. The carbon molecular sieve according to claim 1, characterized in that The heating rate of the calcination is 4-6°C / min.
Citation Information
Patent Citations
MOFs based carbon dioxide adsorbent, preparation method and application thereof
CN104056598A
Nitrogen-doped porous hollow carbon sphere carbon dioxide adsorption material as well as preparation method and application thereof
CN106861618A